Correlation between headache and psychiatric disorders: A narrative review - Nogueira, Guilherme Nobre; Garcia, Thaís Neri Andrade de Almeida; Barbosa, Flávia Alessandra Mendes; Silva, Nicole Custódio Porto; Costa, Marianna Cassini Soares da; Natan de Araujo; Garcia, Luíza Neri Andrade de Almeida; Garcia, Júlia Neri Andrade de Almeida; Mangas, Gabriel de Moraes; Luiza Curti; Souza, Maria Tereza de Oliveira; Rodrigues, Suzana Patricia Santos; et al. (Headache Medicine, 2023)
Full abstract in PDF.